COMPARISON OF TWO PARASITOLOGICAL TECHNIQUES FOR THE DIAGNOSIS OF INTESTINAL PARASITES IN A POPULATION OF IBERIAN IBEX (CAPRA PYRENAICA SCHINZ, 1838) IN THE SIERRA DE GUADARRAMA NATIONAL PARK (SPAIN) - Muñoz Araujo, Benito; João da Silva, Zacarias Rosalina; Refoyo Román, Pablo; Olmedo Salinas, Cristina (Archives of Veterinary Science, 2020)
Twenty samples of Iberian ibex collected in October 2014 in Sierra de Guadarrama National Park (Spain) were analyzed to evaluate detectability of intestinal parasites by two concentration techniques: Ritchie (1948) and Anécimo et al. (2012) and also to analyze and compare the parasite catalogue of each technique. There has been a decrease in the diversity of species found and an increase in prevalence data with respect to previous studies carried out in the same area, possibly due to the increase in Iberian ibex density in the area. A nematode species (Nematodirus filicollis) that has not previously been found in the population under study and which typically parasites cattle, has also been identified. This suggests an exchange of parasites between wild ungulates population and domestic livestock in this area. There were no significant differences between the results obtained by the two techniques used so that, the improvement in the working conditions of the analysts that involves the use of the Anécimo technique by not using hazardous solvents to health, can serve as a guideline to change the protocol of action.